Experimental Evaluation of Performance of Different Thermal Boxes Heated by Solar Radiation for Hot Water Storage System - M.Y, YUHAZRI; A.M, KAMARUL; S.H, YAHAYA; A.H, RAHIMAH; M.N, MASLAN; M, HAIRUL EFFENDY; HAERYIP, SIHOMBING (2012)
The aim of this research is to investigate the performance of different thermal boxes heated by solar radiation for a water storage system that can be used in accordance with the climate of Asia-Pacific countries. In general, this research is related to thermal efficient water heating system, specifically to improve the water heating system that exists nowadays. The focus is to improve the thermal efficiency by adding different thermal boxes as the absorber bed. By implementing the black body and radiation concept, the air trapped in the box is heated. The trapped air then increases the collisions between the molecules and directly increases the temperature inside the box, higher than the outside environment. Based on theory and concept purposed, the temperature of the water increases more efficient and faster by using radiation heat as the source. Based on 24 hours experimental results revealed steel thermal box is better to be used for tropical weather like Malaysia